(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article examines issues related to ensuring public safety during mass events, issues related to the emergence of various serious conflicts, ensuring interethnic disputes in international relations, preventing violations and monitoring offenders.